Small Angle Scattering and Diffraction 2018
DOI: 10.5772/intechopen.76266
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale X-Ray Scattering for Probing Chemo-Morphological Coupling in Pore-to-Field and Process Scale Energy and Environmental Applications

Abstract: One of the greatest challenges of our generation is the sustainable storage of environmentally harmful by-products of energy production processes. High-level nuclear wastes and CO 2 produced from the energy sectors are examples of these by-products. To ensure the environmentally benign storage of these by-products in a solid form, it is essential to understand the chemical and morphological features of the materials in which these byproducts are immobilized. With recent advancements in X-ray scattering, it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Furthermore, in situ experimental techniques for determining the time-resolved abundances of solids (including intermediate phases), gases, fluids, and solutes are required to delineate and quantify carbonation and serpentinization reactions under elevated-pressure and -temperature conditions. These techniques are continuing to be developed, as researchers are investigating olivine reactivity under subsurface-relevant conditions with in situ optical, ,,, nuclear magnetic resonance (NMR), and X-ray spectroscopies that complement X-ray scattering and diffraction investigations. ,,,, Experimental advances need to be partnered with computational studies to help unravel key mechanistic information, such as those that provide insight into processes at olivine–H 2 O–CO 2 interfaces , and the thermodynamic stabilities of Mg carbonates. Coupled reactivity and transport during olivine carbonation is also being evaluated with flow-through and diffusion-limited experimental setups , that simulate a range of realistic fluid:rock ratios, flow rates, and pore network , regimes. These studies and others are beginning to clarify physicochemical feedback between olivine carbonation and porosity–permeability development, including how localized flow rates and crystallographic orientation influence preferential carbonate precipitation.…”
Section: Knowledge Gaps and Research Frontiersmentioning
confidence: 99%
“…Furthermore, in situ experimental techniques for determining the time-resolved abundances of solids (including intermediate phases), gases, fluids, and solutes are required to delineate and quantify carbonation and serpentinization reactions under elevated-pressure and -temperature conditions. These techniques are continuing to be developed, as researchers are investigating olivine reactivity under subsurface-relevant conditions with in situ optical, ,,, nuclear magnetic resonance (NMR), and X-ray spectroscopies that complement X-ray scattering and diffraction investigations. ,,,, Experimental advances need to be partnered with computational studies to help unravel key mechanistic information, such as those that provide insight into processes at olivine–H 2 O–CO 2 interfaces , and the thermodynamic stabilities of Mg carbonates. Coupled reactivity and transport during olivine carbonation is also being evaluated with flow-through and diffusion-limited experimental setups , that simulate a range of realistic fluid:rock ratios, flow rates, and pore network , regimes. These studies and others are beginning to clarify physicochemical feedback between olivine carbonation and porosity–permeability development, including how localized flow rates and crystallographic orientation influence preferential carbonate precipitation.…”
Section: Knowledge Gaps and Research Frontiersmentioning
confidence: 99%
“…In addition to providing insights into the changes in the basal spacing of Ca­(OH) 2 , detailed insights into the changes in the pore–solid interface from the Porod slope were obtained using USAXS/SAXS data. , The Porod slope provides information about the “fractal dimensions” of the scattering objects. In this work, the Porod slope was calculated for the q values in the range 0.02–0.2 Å –1 and the fractality of local structure was investigated.…”
Section: Results and Discussionmentioning
confidence: 99%
“…To address these questions, we utilized multiscale in operando X-ray scattering measurements to elucidate the changes in the reactant and product phases with the corresponding textural changes in the materials. The wide angle X-ray scattering (WAXS) measurements provide detailed insights into the evolution of the solid reactant and product phases, while the ultrasmall/small angle X-ray scattering (USAXS/SAXS) measurements show the evolution of textural changes with reaction progress (Figure ). The cross-scale evolution in the structure and morphology of the solid products during bioenergy production integrated with carbon capture, utilization, and storage starting from cellulose and lignin reacted with Ca­(OH) 2 can be effectively probed using in operando USAXS/SAXS/WAXS measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that the properties and transport of confined fluids such as water (Bonnaud et al, 2010;Ho and Striolo, 2015;Hu et al, 2015;Chakraborty et al, 2017), gases such as CO 2 (Chialvo et al, 2012;Striolo and Cole, 2017;Simoes Santos et al, 2018), and hydrocarbons (Cole et al, 2013;Le et al, 2015a,b;Wu et al, 2015;Le T. T. B. et al, 2017;Herdes et al, 2018;Obliger et al, 2018;Simoes Santos et al, 2018) in nanoporous environments differs from bulk behaviors due to changes in the structure and affinity of confined liquids (Wang H. et al, 2016;Johnston, 2017) and gases (Yuan et al, 2015;Sun et al, 2016aSun et al, ,b, 2017Wang S. et al, 2016a,b) for the solid interfaces. With increasing interest in enhanced gas recovery coupled with subsurface CO 2 storage, a fundamental understanding of the changes in the structure of CO 2 and CH 4 and transport properties of these gases through water-bearing nanoporous environments provides a scientific basis for the observed fate and transport of these gases at the field scale (Glezakou and McGrail, 2013;Gadikota et al, 2017;Gadikota, 2018;Gadikota and Allen, 2018).…”
Section: Introductionmentioning
confidence: 99%